Poskus oblikovnega eksperimenta v dramski ustvarjalnosti Franka Wollmana - Zelenková, Anna (Primerjalna književnost, 2017)
The paper examines hitherto unpraised dramas authored by Frank Wollman (1888-1969), a comparatist and member of the Prague Linguistic Circle. Its aim is to evaluate his works with respect to the structural theory of drama, which he professed all his life. It is in particular the newly discovered manuscript of the historic play Fridland, his "opus magnum" completed during the German occupation in 1941-1944, that reveals Wollman's concept of tragedy as a specific literary structure representing intentional givenness of values, aesthetically differentiated and expressed in language. According to Wollman, the dramatic work which exists as an aesthetic object in the spectators' consciousness is solely grounded in the text constituted on "the intersection of several structural layers" with a number of functions and values. In Fridland, Wollman uses the form of historical-balladical chronicle to depict the last period (1631-1634) in the life of Albrecht von Wallenstein, the most notable general in the thirty years' war. In a critical polemic with an earlier dramatic portrayal of this historical personage, namely against the German cultural background (F. Schiller, etc.), he attempted to rehabilitate Wallenstein as a great Czech statesman endeavouring to promote peace. Quite an original play, it was difficult to perceive and never printed, nor staged. In the early 1950s, Marxist historiography saw Wallenstein as a prototype of Czech-German collaborationism. Our comparative analysis of Wollman's theoretical views and his own dramatic pieces positively contributes to understanding the thought contexts of morphological (phenomenological) structuralism which influenced Central European comparative thought in the first half of the twentieth century.
Keywords: Czech drama; češka dramatika; structuralism; strukturalizem; teorija drame; theory of drama; Wollman, Frank, 1888-1969